Extracellular electron transfer from cathode to microbes: application for biofuel production. Issue 1 (December 2016) - Choi, Okkyoung; Sang, Byoung-In
Abstract Extracellular electron transfer in microorganisms has been applied for bioelectrochemical synthesis utilizing microbes to catalyze anodic and/or cathodic biochemical reactions. Anodic reactions (electron transfer from microbe to anode) are used for current production and cathodic reactions (electron transfer from cathode to microbe) have recently been applied for current consumption for valuable biochemical production. The extensively studied exoelectrogenic bacteriaShewanella andGeobacter showed that both directions for electron transfer would be possible. It was proposed that gram-positive bacteria, in the absence of cytochrome C, would accept electrons using a cascade of membrane-bound complexes such as membrane-bound Fe-S proteins, oxidoreductase, and periplasmic enzymes. Modification of the cathode with the addition of positive charged species such as chitosan or with an increase of the interfacial area using a porous three-dimensional scaffold electrode led to increased current consumption. The extracellular electron transfer from the cathode to the microbe could catalyze various bioelectrochemical reductions. Electrofermentation used electrons from the cathode as reducing power to produce more reduced compounds such as alcohols than acids, shifting the metabolic pathway. Electrofuel could be generated through artificial photosynthesis using electrical energy instead of solar energy in the process of carbon fixation.